قيمة الحياة الإنسانية في القرآن الكريم : دراسة موضوعية عن ظاهرة قتل الإنسان - لبابنة، عايش علي محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2001)
Using an exegetic thematic approach to the phenomenon of homicide as expound in the Quranic verses, this study deals with the question of the value of human life in the Holy Quran. The researcher has thus explored the different aspects of the subject. The study has defined the technical meaning of homicide, thus distinguishing it from other similar terms. It has also dealt with the historical dimension of homicide as it has been treated in the Quranic historical accounts Al-Qasas Al -Qurani. By this, it aimed at discovering the historical, intellectual and educational connotations of those accounts. In addition to that, the study has explored the legal aspect of the Quranic verses dealing with homicide as a crime and the eschatological and worldly judgements which the Holy Quran has attributed to it. Meanwhile, the Quranic method has been contrasted with the approaches of the different legal schools Madhahib. Then, the study has addressed homicide as a punishment itself Here, it tried to show the instances where the killing of a human being is declared legal and the wisdom behind that. In this connection, the study discussed some of the psychic and social aspects of homicide in the Quranic perspective. The study has thus shown the high measure the Quran attaches to human life as well as the perfect character of its legislation in dealing with the protection of that life. It has also shown the characteristics of the balanced Quranic approach that is at the same time compatible with human nature and personality as well as the established scientific truths. This study has thus demonstrated the importance of thematic exegesisal-Tafsir alMawdui in dealing with the different aspects of human phenomena